Fórum de discussão estudantil (FDE) - Barberis, Maria Beatriz [UNESP]; Cecílio, Matheus de Freitas [UNESP]; Farias, Anna Carolina Monéia [UNESP]; Poker, José Geraldo Alberto Bertoncini [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The Student’s Discussion Forum is an extension program realized since 2009 by the Group of Study and Research in International Organizations (GEO), connected to the College of Philosophy and Sciences of Unesp, campus of Marília. The Forum consists on the promotion of model simulations based on the meetings of the Organization of American States (OAS). The simulations are offered to the high school students of the public and private education systems of Marília. With the help of the teachers related to the subject, such as History, Geography, Sociology and Philosophy; the high school students are invited to act as delegates of the countries of the OAS, debating and promoting solutions to continental problems, notably those related to Human Rights, Environment and Sustainability. In order for them to be able to participate in the discussions, the high school students receive capacitation from the International Relations graduation students of Unesp, who, in turn, are orientated by the students related to the Social Sciences Post-Graduation Program of the same unit.

O Forum de Discussão Estudantil é uma atividade de extensão universitária realizada desde 2009 pelo Grupo de estudo e pesquisa em Organizações Internacionais (GE0), vinculado à Faculdade de Filosofia e Ciências da Unesp, campus de Marília. O Forum consiste na promoção de simulações de reuniões que ocorrem no âmbito da Organização dos Estados Americanos (OEA). As simulações são dirigidas a estudantes do ensino médio, frequentadores de escolas da rede pública e privada no município de Marília. Mediante o auxílio de professores de História, Geografia, Sociologia e Filosofia que trabalham nas escolas, os alunos do ensino médio são convidados a atuar como delegados dos países membros da OEA, debatendo e propondo soluções para problemas que afetam o continente, notadamente aqueles vinculados às problemáticas dos Direitos Humanos, ambiente e sustentabilidade. Para que consigam participar das simulações, os estudantes do ensino médio recebem capacitação de alunos do curso de graduação em Relações Internacionais da FFCUnesp, que por sua vez são orientados por alunos do Programa de Pós-Graduação em Ciências Sociais da mesma Unidade.
Keywords: Simulation; OAS; Human rights; Simulação; OEA; Direitos humanos